Heterocyclic Polymers Perspectives in Nanolayers of Donor Acceptor Heterojunction for Organic Photovoltaic Application - M.N. Orlova; S.I. Didenko; O.I. Rabinovich; D.S. Saranin (Журнал нано- та електронної фізики)
The possibility of molecular structural design provides a wide field for engineers to generate interest to heterocyclic structures based on die-perylene and naphthoyl, the possible combinations for the superposition of the absorption spectra. From this point of view, the creation of optically active polymers based on polybenzomidazofenantroline (PBF), 1, 4, 5, 8- naphthalene tetracarboxylic and 3, 4, 9, 10- perylenetetracarboxylic acids opens new opportunities in this important field of science and technology. The results are high absorption in visible spectrum and ability of morphology improvement. Advantages in the optical properties PPBI-O and PNBI-O above the target prototype P3HT, namely a peak absorption in the region of 555 nm to 700 nm red edge are detected.